Internet censorship detected in Tanzania (Tanzania) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Tanzania. Data sourced from CensoredPlanet.
Censorship Incident ID: TZ-2026-0040. Severity: critical. Confidence: 65%